Hermann Jakob Czernin von Chudenitz’ Diplomatic Mission in Warsaw in 1695. A Contribution towards the Travel Arrangements of Imperial Diplomats - Jiří Kubeš (Theatrum Historiae)
This paper examines the previously unknown diplomatic mission of Hermann Jakob Count Czernin von Chudenitz in Warsaw in 1695. Neither Polish nor Czech nor Austrian historians paid any attention to it. Based on this, however, it is possible to demonstrate perfectly how tense the relations between Emperor Leopold I and the Polish King John III Sobieski, who, at the end of their lives, were officially allies in the Holy League. The author first briefly introduces this mission and then, using it as an example, attempts to show how the travels of the imperial ambassadors of that time were organised and also unveils other additional aspects of the diplomatic service. Above all he reconstructed the court of Count Czernin, who was surrounded by over 80 people, and also located the place of his accommodation in Warsaw and showed which apartment the Count possessed as an ambassador. Finally, he examined the question of the financial costs of this stay, and documented the fact that the ambassador had to pay many expenses from his own pocket, and that this mission had cost him cca. 50,000 guldens.